Promotion of Physical Activity focusing health. - P. Tercedor; M. J. Jiménez; B. López (Asociación Española de Ciencias del Deporte, 2010)
Health protection and promotion is a social issue since sedentary life is increasing as society develops. Physical activity is considered to be a fundamental means for achieving the goal of health protection and promotion. In this paper the roles of several institutions and personalities in such an achievement are assesed as well as the various aspects concerning physical activity as a means for enhancing health. The possibilities of participation of health professionals and the role of the education system in promoting physical activity are analysed as well. KEY WORDS: Health, promotion, physical activity, education